A 'dynamic' landscape of fear: prey responses to spatiotemporal variations in predation risk across the lunar cycle. (12th September 2017) - Palmer, M. S.; Fieberg, J.; Swanson, A.; Kosmala, M.; Packer, C.
Abstract: Ambiguous empirical support for 'landscapes of fear' in natural systems may stem from failure to consider dynamic temporal changes in predation risk. The lunar cycle dramatically alters night‐time visibility, with low luminosity increasing hunting success of African lions. We used camera‐trap data from Serengeti National Park to examine nocturnal anti‐predator behaviours of four herbivore species. Interactions between predictable fluctuations in night‐time luminosity and the underlying risk‐resource landscape shaped herbivore distribution, herding propensity and the incidence of 'relaxed' behaviours. Buffalo responded least to temporal risk cues and minimised risk primarily through spatial redistribution. Gazelle and zebra made decisions based on current light levels and lunar phase, and wildebeest responded to lunar phase alone. These three species avoided areas where likelihood of encountering lions was high and changed their behaviours in risky areas to minimise predation threat. These patterns support the hypothesis that fear landscapes vary heterogeneously in both space and time.